PAH metabolites in bile of European eel (Anguilla anguilla) from Morocco - Wariaghli, Fatima; Kammann, Ulrike; Hanel, Reinhold; Yahyaoui, Ahmed (Bulletin of Environmental Contamination and Toxicology, 2015)
Environmental pollution of fish with organic contaminants is a topic of rising attention in Morocco. Polycyclic aromatic hydrocarbons (PAH) are prominent organic contaminants which are rapidly metabolized in fish. Their metabolites are accumulated in the bile fluid and can be used to assess PAH exposure. The two PAH metabolites 1-hydroxypyrene and 1-hydroxyphenanthrene were quantified in European eels (Anguilla anguilla) from two Moroccan river systems by high-performance liquid chromatography with fluorescence detection. Mean values ranged from 52 to 210 ng/mL 1-hydroxypyrene and from 61 to 73 ng/mL 1-hydroxyphenanthrene. The overall concentrations of PAH metabolites in eel from Morocco appeared moderate compared to eel from European rivers and coastal sites. The present study provides first information on concentrations of PAH metabolites in fish from Morocco.